The Circular Economy: A New Industrial Environmental System for the Application of Comprehensive Sustainability Standards - شامية, بن عباس (Milev Journal of Research and Studies, 2019)
The paper aims to highlight the adverse effects of global industrial economic systems have become things are known to all, prompting researchers to seek alternatives and seek solutions between industrial necessity and the need to preserve the rest of the sound environment, through the development of the system of recycling economy or circular economy which calls for the continuous reuse of resources by re-using and renewing products, components and materials and making them more sustainable. switch to using environmentally friendly systems, most notably the circular economy, which is one of the most strategic issues in the coming years and is designed to rely on innovation and the dissemination of flexible economic models, in order to reduce greenhouse gas emissions and pollution, ensuring more healthy years of life on Earth.